Antioxidant Potential of Ethanolic and Aqueous Extracts of Selected Medicicinal Plants on Fungal Species - Agbagwa, Obakpororo Ejiro; Joseph, O. V.; Frank-Peterside, N. (European Journal of Applied Sciences, 2022)
Medicinal plants are plants in which at least one of its parts possesses therapeutic properties that are useful for the treatment of aliments. The study was carried out to determine the antioxidant potential of Borreria verticillata, cassia alata, Carica papaya, Diodia Sarmentosa, and Ocimum gratissimum on Rhizopus oryzae, Aspergillus tamarii, Tricholoma matsutake, Kodamaea ohmeri, Aspergillus awamori , Aspergillus fumigatus, Aspergillus nomius, Aspergillus awamori and Aspergillus nomius. The five medicinal plants were collected from University of Uyo botanical garden, while the nine fungal isolates were stock cultures from previous studies. The leaves of the five plants were extracted by ethanolic and aqueous methods, and subjected to phytochemical screening. The extracts were also subjected to antifungal assay by the agar diffusion methods. Results obtained on the phytochemical screening of leaf extracts indicated the presence of alkaloids, tannins, saponins, terpenes, flavonoids, salwoski, Keller-killian, liberman, gyanogenetic glycosides, phlobactanin, and free and combined anthraquinone in varying quantities. The antifungal assay of the aqueous and ethanolic leaf extract for all the plants at five different concentration (31.25mg/ml,62.5mg/ml,125mg/ml,250mg/ml and 500mg/ml), showed that that Cassia alata(14mm ethanol,10.67mm aqueous) had the highest inhibition zone, which was followed by Ocimum gratissimum (12.89mm ethanol,and 10.56 aqueous), Diodia sarmentosa (12.87mm ethanol and 8.22mm) and Borreria verticillata (12.44mm ethanol and 7.78mm aqueous). The lowest inhibition was observed in Carica papaya (11.78mm ethanol and 6.56mm aqueous) at concentration 500mg/ml. Minimum inhibitory concentration obtained ranged between 31.25-125mg/ml. Generally, ethanolic extract were more effective than aqueous extract, although all the plant had inhibitory effect in both solvents. The outcome of the work justifies the use of these plants in ethno-medicine.